2016
DOI: 10.1039/c6ob01772j
|View full text |Cite
|
Sign up to set email alerts
|

A solid-phase synthetic approach to pH-independent rhodamine-type fluorophores

Abstract: An efficient methodology using the Fukuyama-Mitsunobu reaction was successfully applied to prepare various Rhodamine B-based amides with the locked possibility to form a lactam ring. The procedure was developed for solid-phase synthesis, which can be advantageously applied to the synthesis of chemical libraries in a combinatorial fashion. A series of derivatives including aliphatic as well as aromatic rhodamine amides alkylated via a reaction with various alcohols were synthesized, and their spectral propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The synthesis is based on the knowledge reported earlier for similar systems with one rhodamine dye. 19,20 We extended the reported synthesis for further reaction sequences and bound another rhodamine moiety (Schemes 1 and 2). 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis is based on the knowledge reported earlier for similar systems with one rhodamine dye. 19,20 We extended the reported synthesis for further reaction sequences and bound another rhodamine moiety (Schemes 1 and 2). 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This alkylation should block the spirolactam cyclization of one rhodamine moiety, assuring to keep fluorescence regardless of the analyte pH. The synthesis is based on the knowledge reported earlier for similar systems with one rhodamine dye. , We extended the reported synthesis for further reaction sequences and bound another rhodamine moiety (Schemes and ).…”
Section: Resultsmentioning
confidence: 99%
“…The oily nitro derivatives 9, 12, and 16 were dissolved in acetic dered zinc (0.5 g) was added. The reaction mixture was stirred at ro h to obtain dihydropteridinones 1, at room temperature for 3 pyrrolopteridinones 2, and at 80 °C for 3-13 h to obtain pyrimidod lution was filtered, evaporated to dryness, and purified by column 25 (m, 6H), 0.87 (t, J = 6.9 Hz, 3H). 13…”
Section: Reduction With Simultaneous Cyclization and Isolation (Compomentioning
confidence: 99%
“…[6,13] Solid-phase chemistry for efficient synthesis of Nalkylated rhodamine amide derivatives developed by Brulikova et al exhibited high photostability, pH-independent features, and practical utility as sensors in a biological application. [14] Csuk et al reported the cytotoxic effects of ester and amide derivatives of RHB on different human tumor cell lines which revealed lesser EC 50 values as low as 0.23 and 0.15 μM for ethyl and hexyl ester, against MCF-7 tumor cells, with lack of selectivity; alternatively morpholinyl derived RHB amide showed good selectivity, but not as cytotoxic as RHB ester, i. e., EC 50 is 0.44-3.76 μM for MCF-7 breast adenocarcinoma cells, furthermore could not explain the selectivity behavior of simple morpholinyl compounds in contrast to the complex triterpenoids. [15] Lately, B.…”
Section: Introductionmentioning
confidence: 99%
“…Solid‐phase chemistry for efficient synthesis of N ‐alkylated rhodamine amide derivatives developed by Brulikova et al. exhibited high photostability, pH‐independent features, and practical utility as sensors in a biological application [14] . Csuk et al.…”
Section: Introductionmentioning
confidence: 99%